SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF SOME 5-AMINO-2-MERCAPTO-1,3,4-THIADIAZOLE DERIVATIVES THIOETERS AND SCHIFF BASES - RAD, Oana; TIBOR, Rózsa; DUMA, Mihaela; VLASE, Laurian; PÎRNĂU, Adrian; TIPERCIUC, Brînduşa; IONUŢ, Ioana; ONIGA, Ovidiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Starting from 5-amino-2-mercapto-1,3,4-thiadiazole, 23 compounds, Schiff bases and S-mercapto-substituted derivatives were synthesized. Their structural elucidation was based on elemental analysis, mass spectrometry and proton nuclear magnetic resonance spectroscopy (¹H NMR). The screening of the antimicrobial activity of the title compounds was realized using the diffusimetric method against several strains of Gram-positive and Gram-negative bacteria and one fungal strain (Candida albicans). Some of the molecules showed moderate to good antibacterial activity against Gram-negative (S. typhimurium, E. coli) and better activity against Gram-positive (B. cereus, L. monocytogenes, S. aureus) bacterial strains. All compounds exhibited moderate to very good activity against C. albicans. Qualitative relationships (SAR) were also established between the chemical structures and the antimicrobial activity of these compounds.